2011
DOI: 10.1093/sleep/34.1.99
|View full text |Cite
|
Sign up to set email alerts
|

Decision Making in Narcolepsy with Cataplexy

Abstract: We demonstrated a lack of perseverance and a selective reduced performance on decision making under ambiguity in NC in contrast to normal decision making under explicit conditions. Patients with narcolepsy-cataplexy may opt for choices with higher immediate emotional valence, regardless of higher future punishment, to compensate for their reduced reactivity to emotional stimuli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 33 publications
4
32
1
Order By: Relevance
“…This parallels our animal studies showing activation of Hcrt neurons during positively motivated tasks, but not during negatively motivated tasks 5 . The current results, in concert with these prior animal and human studies suggest that depression and reported difficulties with social interaction in narcolepsy and Parkinson’s 35 may be related to the loss of Hcrt cells in both of these conditions 2, 14, 36 . However, we cannot eliminate the indirect role of the disability that accompanies these disorders in generating depression in humans.…”
Section: Discussionsupporting
confidence: 77%
“…This parallels our animal studies showing activation of Hcrt neurons during positively motivated tasks, but not during negatively motivated tasks 5 . The current results, in concert with these prior animal and human studies suggest that depression and reported difficulties with social interaction in narcolepsy and Parkinson’s 35 may be related to the loss of Hcrt cells in both of these conditions 2, 14, 36 . However, we cannot eliminate the indirect role of the disability that accompanies these disorders in generating depression in humans.…”
Section: Discussionsupporting
confidence: 77%
“…Cognitive performance has been difficult to assay in narcolepsy due to the confounding effect of sleepiness. Sleep, however, remains restorative and phasic arousal is preserved in patients (70), and sleepiness-independent deficits were reported, including impaired perceptual encoding of stimuli, attention deficits in executive tasks, and impaired decision making (70)(71)(72). Neural substrates underlying sleepiness and subjective perception of sleep propensity while awake are largely unknown.…”
Section: Tdw State Heterogeneity: Hcrt Loss Finely Alters the Tdw Oscmentioning
confidence: 99%
“…Other studies have found that patients with narcolepsy have particular difficulties in tasks that put high demands on monitoring and manipulation of information (ie, in tasks that require a high degree of executive control) [17,18]. Recent investigations have pointed to changes in decision-making, information sampling, and reward sensitivity [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%